Factores climáticos relacionados con el comportamiento epidemiológico del dengue en las provincias de El Oro, Loja y Zamora Chinchipe, periodo 2014-2023 - Armijos Peña, Shandry Daniel (2025)
The control of vector-borne diseases, such as dengue, is a significant global public health challenge, accounting for 17% of infectious diseases and causing approximately 700,000 deaths annually. In South America, dengue is prevalent in tropical climates, with a notable increase in reported cases in 2022 and 2023, especially in Bolivia and El Salvador, where national alerts have been declared. This research focuses on the epidemiological temporospatial behavior of dengue in the provinces of El Oro, Loja and Zamora Chinchipe, Ecuador, during 2014-2023, analyzing its relationship with climatic factors such as temperature, humidity and precipitation. A quantitative approach was used with an observational design and statistical analysis using SPSS software. The results revealed that 19,010 cases of dengue fever were recorded in zone 7, with a higher prevalence in El Oro (79.94%). A significant relationship was identified between climatic factors and the incidence of dengue, where constant temperatures and moderate rainfall favored the proliferation of the Aedes aegypti vector. The findings underscore the need to implement preventive strategies based on interactive communication, which have proven to be effective in reducing cases in communities. This study provides valuable information for the development of public health policies and community education programs aimed at mitigating the risk of dengue fever